Analisis Faktor Kepuasan Kerja Perawat Rumah Sakit Nasional Diponegoro Semarang - Aryudi, Dwinda Rahmawati; Suryawati, Chriswardani; Nandini, Nurhasmadiar (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The World Health Organization estimates that in 2030, there will be a shortage of nurses, especially in developing countries, due to job dissatisfaction. Human resources in hospitals are dominated by nurses, so it is important to pay attention to nurse job satisfaction. Diponegoro National Hospital must focus on nurse job satisfaction because there has been an increase in nurses' resignations over last three years (2019–2021). The study was conducted to determine the factors associated with job satisfaction among nurses at the Diponegoro National Hospital. In this cross-sectional study, 97 nurses at Diponegoro Hospital were surveyed using a total sampling technique. Univariate analysis was presented with a frequency distribution table and bivariate analysis was based on chi-square statistics. The results showed there was a relationship between job satisfaction and awards (p = 0.010), promotion opportunities (p = 0.003), and hospital policies (p = 0.042). There was no association between job satisfaction and compensation (p = 0.527), interpersonal relationships (p = 0.057), or job security (p = 0.093). In conclusion, it was found that awards, promotions, and hospital policies are related to job satisfaction among nurses at Diponegoro National Hospital. It is expected that there will be improvements in the nurse reward program, improvements in the promotion system, evaluating promotion policy socialization, providing training and education needed by nurses for career advancement, evaluating the policy socialization system, evaluating the compensation system, and efforts to minimize interpersonal conflicts in the hospital.